Peculiarities Of Clinical Picture Of Necrotic Infections Of Soft Tissues In Patients With Diabetes Mellitus (Texas Journal of Medical Science, 2024)
The review presents data on the peculiarities of the clinical picture and course of necrotic infections of soft tissues against the background of diabetes mellitus, and highlights the issues of diagnosis. Characteristic clinical signs of inflammation that accompany surgical infection are not always manifested at early stages. This is especially pronounced in patients suffering from diabetes mellitus. The necessity of creating a unified diagnostic algorithm in case of suspicion of this pathology is substantiated. Thus, surgical soft tise infection, in particular necrotic lesions in patients with diabetes mellitus remain one of the urgent problems of modern medicine, in solution of which early clinical diagnostics and further therapeutic tactics are of great importance